Espousing Democratic Leadership Practices: A Study of Values in Action - Devereaux, Lorraine (Alberta Journal of Educational Research, 2003)
This article examines principals' espoused values and their values in action. It provides a reanalysis of previously collected data through a values lens. The original research study was an international quantitative and qualitative investigation of principals' leadership approaches that was based in 75 schools. This particular excerpt of the research provides a qualitative lens into two European principals' espoused values versus values in action in a site-based management environment. The study demonstrates that principals' espoused values can be different from their values in action as perceived by themselves and others. This has implications for the practical application of modern school restructuring site-based management theory, and it shows the need for a value-based component to principals' leadership training.